"Human Spirit" — Visionary Project: Breakthrough for Psychoanalysis — Preservation for Buddhism: A Global Promise for Psychoanalytic Contribution for Weakened Populations. Issue 7 (2nd October 2020) - Kulka, Raanan; Gavrieli-Rahabi, Iris; Goldberg, Karina
ABSTRACT: Within the vibrant web of general Israeli psychoanalysis, the Israeli community of self psychology, grounded within Kohutian foundations, has developed an ethical-theoretical shift that can be termed selfobject psychology, a sort of bold proposal to spiritual psychoanalysis. This development enhances the Kohutian revolution of transforming psychoanalysis from the empirical sphere of the positivistic sciences onto an experiential realm of contemplative science. We believe that merging Buddhist philosophy and methodologies within a unique program of psychoanalytic training will impel an evolutionary process that will transform the whole domain of psychoanalysis – philosophically, paradigmatically, and clinically. 'Human Spirit' Psychoanalytic-Buddhist Training Program is a framework for psychoanalysts who are immersed in nurturing and refining the spiritual dimension of the mind. The program strives to cultivate a compassionate, transformed and unified psychoanalytic presence, oscillating freely between the personal, the interpersonal, and the transpersonal dimensions of the psychoanalytic space.